STUDI ALIH–FUNGSI CFB BOILER SEBAGAI PEMBANGKIT CO–GENERATION - Rahardjo, Bambang Suwondo (Jurnal Sains dan Teknologi Indonesia, 2007)
Demo–plant CFB boiler 30 ton steam/hour is a granted equipments of cooperation program between BPPT and NEDO Japan in technological study area of CFB Boiler to utilize low–rank coal which functioned as steam consumption supply as well as electricity at production process system in Paper Mill of Basuki Rachmat – Banyuwangi. But outside calculation in the year of 1998, Indonesia occured economic crisis which result activity of construction which have 90% perforced to be discontinued, because PKBR as area owner and construction funder expressed have national debt, so that the asset taken over by BPPN. Since the project activities discontinued, various effort of project solving have been conducted, one of them, BPPT propose study of CFB Boiler displace function as steam and electricity generation (co–generation). In this paper, writer try to elaborate result of study giving 5 option, that is (1) Stand–alone power station, (2) Co–generation 1 (new steam turbine), (3) Co–generation 2 (new steam turbine+cooling tower), (4) Co–generation 3 (existing steam turbine) and (5) Co–generation 4 (existing steam turbine+cooling tower).